High-risk cutaneous malignancies and immunosuppression: Challenges for the reconstructive surgeon in the renal transplant population. Issue 7 (July 2017) - Kearney, L.; Hogan, D.; Conlon, P.; Roche, M.; O'Neill, J.P.; O'Sullivan, J.B.
Summary: Renal transplantation is the most frequently performed transplant procedure. Immunosuppressive therapies have dramatically increased survival rates in transplant recipients but are associated with an increased risk of skin cancers. Recent changes in immunosuppressive strategies have been adopted with the aim of reducing this challenging adverse effect. Despite these new strategies, cutaneous malignancies tend to be numerous, aggressive and associated with a higher risk of local and distant dissemination than in the non-transplant population. This represents a significant workload for transplant physicians, dermatologists, and head and neck and plastic surgeons. This review highlights key concepts in the pathogenesis of skin cancer in transplant patients, the impact current and evolving immunosuppressive strategies and regimens will have on the epidemiology, and the management of cutaneous malignancies in renal transplant patients, with particular focus on the implications for the plastic surgery community.